Triple G-C-T base-coded self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications - Singh, Dharmendra; Gone, Nilu V.; Bandi, Kiran; Davis, Disiya; Nair, Kiran Sukumaran; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2025)
We report self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications. These nucleobase monomers are adorned with nature-inspired triple G-C-T nucleobases featuring three recognition sites: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Using readily accessible starting materials, these monomers can be synthesized in excellent yields, making them good choices for diverse applications. Their unique structural features, coupled with their water solubility, may offer exciting opportunities for the creation of new biomaterials.

Design, synthesis, and adhesive performance evaluation of DOPA-Functionalized polyurethane elastomers - Davis, Disiya; Alam, Md Shafi; Purushothaman Bindu, Bhadra; Lakshmi, Durga; N Muhammed, Hasin; Torris, Arun; Ambade, Ashootosh V.; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Functional polyurethane (PU) hot-melt adhesives were developed through the incorporation of a dopamine-derived chain extender (DADO) into thermoplastic PUs. The DADO monomer was synthesized via a four-step route and successfully integrated into the PU backbone using a one-pot, two-step polymerization involving polycaprolactone-diol and 4,4 `-methylenebis(phenyl isocyanate). Spectral analyses confirmed the formation of urethane linkages and the effective incorporation of catechol moieties. Monomodal molecular weight distributions were obtained through size-exclusion chromatography with Mn ranging from 12,000 to 17,000 g/mol. Thermal analyses demonstrated two-step decomposition behavior and a progressive increase in glass transition temperature with increasing DADO content. Mechanical testing revealed that there was substantial improvement in the tensile strength of these materials from 1.34 MPa for unmodified PU (PU-0) to 14.3 MPa for PU-10. Adhesion performance exhibited a similar trend, with PU-10 attaining the highest lap-shear strength of 3.92 +/- 0.19 MPa on the Al substrate. PU-10 exhibited the highest lap-shear strength of 3.92 +/- 0.19 MPa on aluminum and superior underwater stability with a value of 2.78 +/- 0.47 MPa compared to other formulations. Overall, controlled incorporation of DADO significantly enhances properties, and PU-10 represents the optimal formulation for high-performance hot-melt PU adhesives.
Keywords: chain extender; dopamine; hot-melt adhesive; polycaprolactone diol; polyurethanes